2018
DOI: 10.1002/navi.272
|View full text |Cite
|
Sign up to set email alerts
|

LTE receiver design and multipath analysis for navigation in urban environments

Abstract: Mitigating multipath of cellular long‐term evolution (LTE) signals for robust positioning in urban environments is considered. A computationally efficient receiver, which uses a phase‐locked loop (PLL)–aided delay‐locked loop (DLL) to track the received LTE signals, is presented. The PLL‐aided DLL uses orthogonal frequency division multiplexing (OFDM)–based discriminator functions to estimate and track the time‐of‐arrival. The code phase and carrier phase performances in an additive white Gaussian noise (AWGN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(62 citation statements)
references
References 46 publications
(107 reference statements)
0
57
0
Order By: Relevance
“…Experimental results show a root mean square error (RMSE) of 3.17 m, a standard deviation of 1.06 m, and a maximum error of 6.58 m between the proposed LTE receiver and the GPS navigation solution over a 1.44 km trajectory. The accuracy of the obtained pseudoranges with the proposed receiver is compared against two algorithms: estimation of signal parameters by rotational invariance techniques (ESPRIT) and EKAT (ESPRIT and Kalman filter) …”
Section: Congratulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental results show a root mean square error (RMSE) of 3.17 m, a standard deviation of 1.06 m, and a maximum error of 6.58 m between the proposed LTE receiver and the GPS navigation solution over a 1.44 km trajectory. The accuracy of the obtained pseudoranges with the proposed receiver is compared against two algorithms: estimation of signal parameters by rotational invariance techniques (ESPRIT) and EKAT (ESPRIT and Kalman filter) …”
Section: Congratulationsmentioning
confidence: 99%
“…The accuracy of the obtained pseudoranges with the proposed receiver is compared against two algorithms: estimation of signal parameters by rotational invariance techniques (ESPRIT) and EKAT (ESPRIT and Kalman filter). 13…”
mentioning
confidence: 99%
“…Several code phase-based receivers have been proposed to obtain the pseudorange measurements from LTE signals [13,[26][27][28]. Analytical and experimental results have shown that the performance of these receivers significantly degrades in multipath environments, making them practically unusable in indoor environments [14,17,29]. In this section, a receiver structure is proposed, which exploits the carrier phase measurements of LTE signals.…”
Section: Lte Receiver Architecturementioning
confidence: 99%
“…2 shows the block diagram of the proposed receiver. This receiver is adapted from the receiver developed in [14], which used a phase-locked loop (PLL)-aided delaylocked loop (DLL). Here, only phase tracking is performed (i.e., code tracking is not utilized) since it was observed experimentally that such tracking indoors degrades the receiver's performance.…”
Section: Lte Receiver Architecturementioning
confidence: 99%
See 1 more Smart Citation